De Pictures from a Life à Letters from a Life : exaltation de la vie de Benjamin Britten - Gilles Couderc (Revue LISA)
To this day Britten’s friend and publisher, Donald Mitchell, once considered his official biographer, has never completed the biography the composer wished him to write, with the express condition that Mitchell tell the truth about him and his lifelong friend, Peter Pears. Mitchell has published a picture biography of Britten, Pictures from a Life, and the composer’s letters and diaries, under the title Letters from a Life, both exalting the life of the hard-working musician, whom Mitchell clearly believes to be one of the twentieth century’s greatest composers. Both works present the same double portraits of Britten and Pears by major photographers, as if duplication could not be avoided. This study examines the image that Lotte Jacobi and Cecil Beaton try to give of Britten and Pears, the meanings that Mitchell seems to have invested the portraits with, how he uses them to recall Britten’s life and times, and finally how the portraits work toward an identification of Britten and Schubert, thus enabling Mitchell to secure Britten’s place among the greatest.